The effects of neutralized palm oil methyl esters (NPOME) on performance and emission of a direct injection diesel engine - Abdul Aziz, Azhar; Said, Mohd. Farid; Awang, Mohamad Afiq; Said, Mazlan (2006)
The used of palm oil-based biodiesels have been proposed as an alternative fuel for diesel engines in Malaysia. The purpose of this study is to investigate the performance and exhaust emissions of various blends of neutralized palm oil methyl ester (NPOME) in a small-unmodified direct-injection diesel engine and to compare them with that of a reference diesel fuel (D2). The NPOME has been blended together with D2 in several percentages (10%, 20% and 50%) and known as B10, B20 and B50. The acquisition of operating parameters such as performances, emission concentrations, cylinder pressure and fuel line pressure were performed as a function of engine loads, at the engine speed of 1500 rpm. The effect of engine load and blend percentages on brake specific fuel consumption (BSFC), brake thermal efficiency, heat release, cylinder pressure, ignition delay, carbon monoxide (CO), carbon dioxide (CO2), unburned hydrocarbon (HC), nitrogen oxide (NOx) and exhaust smoke were carried out in this study. As a whole it was found that the palm oil-based alternatives behaved comparably well to the D2 in terms of performance (fuel consumption and thermal efficiency). Smoke density readings show improvements as compared to that emitted by the diesel fuel in which operating under similar conditions. The emissions of CO, CO2 and HC were reduced by using biodiesel fuels, while NOx emissions for biodiesels were slightly higher.